The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/hpm.2790
|View full text |Cite
|
Sign up to set email alerts
|

Urgent care centre in Swedenthe integration of teams and perceived effects

Abstract: Summary An urgent care centre (UCC) is an upcoming trend in Swedish health care. Although UCCs have been established in other countries, their effectiveness and value have not yet been studied in Sweden. The aim of this study was to investigate the interaction between the UCC and emergency department (ED) by using validated evaluation models. One adult ED (AED) and one child ED (CED), together with a newly established UCC nearby, were included in this study. The interaction between the UCC team and the ED team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
(80 reference statements)
0
9
0
2
Order By: Relevance
“… 12 , 13 Swedish ED personnel, after the formation of a nearby UCC, did report subjective capacity pressure reduction. 14 A Chilean study also reported a minor (2.7%) reduction in ED visits after UCC establishment. 15 A study of six American states demonstrated a 17.2% reduction in ED visits during times when UCCs in the corresponding zip code were open.…”
Section: Resultsmentioning
confidence: 95%
“… 12 , 13 Swedish ED personnel, after the formation of a nearby UCC, did report subjective capacity pressure reduction. 14 A Chilean study also reported a minor (2.7%) reduction in ED visits after UCC establishment. 15 A study of six American states demonstrated a 17.2% reduction in ED visits during times when UCCs in the corresponding zip code were open.…”
Section: Resultsmentioning
confidence: 95%
“…Um estudo sueco, que investigou a interação entre um Centro Atendimento de Urgência (UCC) e emergências hospitalares adulto e pediátrica, identificou como desafio: fazer com que os profissionais de ambos os serviços se conhecessem, o que diminuiria as controvérsias e aumentaria a confiança entre as equipes. Explicase que os UCC são serviços de saúde, tipicamente compostos por médicos, enfermeiros e auxiliares de Enfermagem, que funcionam no nível intermediário de cuidados à saúde, entre as emergências hospitalares e a atenção primária 15 , similares às UPA brasileiras.…”
Section: Discussionunclassified
“…Na Suécia, um estudo revelou que, mesmo que houvesse uma diretriz baseada no diagnóstico e na gravidade, regulando a distribuição dos pacientes entre os Departamentos de Emergência hospitalares e o UCC, ainda haveria certa ambiguidade sobre como interpretá-la, julgando-se necessário recrutar pessoal com longa experiência em triagem para evitar erros 15 .…”
Section: Discussionunclassified
“…Questions about the parties' capacity for diagnosing and treating patients were sorted out, and non-conventional solutions were occasionally invented to handle strenuous situations and tricky cases. Mistakes in assessments and patients whose health conditions rapidly changed could easily be handled by swift re-referrals from the UCC back to the ED [17].…”
Section: Discussionmentioning
confidence: 99%
“…Doran showed that patients treated by UCCs, sited together with and in close collaboration with an ED, received swift service and better follow-up than the control group in the study [16]. UCCs and EDs have also proven to be horizontally integrated and collaborative and function informally between ED and UCC staff [17].…”
Section: Introductionmentioning
confidence: 96%